Perceived health facility-related barriers and post-abortion care-seeking intention among women of reproductive age in Osun state, Nigeria - Tosin Olajide Oni; Stephen Ayo Adebowale; Anuoluwapo Adeyimika Afolabi; Akanni Ibukun Akinyemi; Olufunmilayo Olufunmilola Banjo (BMC Women's Health, 2023)
Abstract Background Post-abortion care (PAC) prevents death and complications caused by unsafe abortion which is widespread in Nigeria. Yet, there is sparse community-based evidence on women’s intention to seek PAC should they have an abortion. This study examined the influence of perceived health facility-related barriers (HFRB) on post-abortion care-seeking intention (PACSI) among women of reproductive ages in Osun state, Nigeria. Methods The study focused on women in a sexual relationship and who were residents of Osun state. A community-based survey was implemented using a multi-stage sampling technique. The calculated sample size (with attrition) was 1200 and data were collected from women aged 15-49 years, using open data kit (ODK). However, 1,065 complete responses were received on the ODK server, indicating an 88.8% response rate. Models were estimated using ordered logistic regression (Ologit) (α0.05) and data analysis was performed using Stata 14.0. Results Mean age of the women was 29.3±7.6 years and 34.01% had the intention to seek PAC in health facilities. Lack of service confidentiality and unavailability of equipment specific to abortion were the two most reported barriers that would prevent women from seeking PAC. The adjusted Ologit model showed that respondents with perceived low HFRB had higher odds (aOR=1.60; CI=1.12-2.11) of seeking PAC in the health facility. Also, women who were employed and skilled were more likely (aOR=1.51; CI=1.13-2.01) while women who had PAC support from spouses/partners had higher odds of healthy PACSI (aOR=2.03; CI=1.48-2.78). Other identified predictors of PAC seeking intention included level of education, employment status, and spousal/partner support. Conclusion Perceived lack of trust in service provision and necessary equipment specific to abortion care had a negative influence on women’s PACSI in Osun state. Reassuring health interventions that focus on improving the public perception of healthcare services and confidence to use the facility will likely improve the patronage of health facility for post-abortion care in Osun sate.